Answer:
the answer for this problem is 135
Answer: x=−2
Step-by-step explanation:
x^3+2x^2+3x+6=0
(x+2)(x^2+3)=0
x+2=0 or x^2+3=0
x=−2
Answer:
![F(x) = 2^{x+2} - 6](https://tex.z-dn.net/?f=F%28x%29%20%3D%202%5E%7Bx%2B2%7D%20-%206)
Step-by-step explanation:
To shift a function F(x) a units to the left, we do:
![F(x) = F(x+a)](https://tex.z-dn.net/?f=F%28x%29%20%3D%20F%28x%2Ba%29)
In this problem, we have that:
![F(x) = 2^{x}](https://tex.z-dn.net/?f=F%28x%29%20%3D%202%5E%7Bx%7D)
So, shifting 2 units left:
![F(x) = 2^{x+2}](https://tex.z-dn.net/?f=F%28x%29%20%3D%202%5E%7Bx%2B2%7D)
Then
To shift a units down, we do:
![F(x) = F(x) - a. So[tex]F(x) = 2^{x+2}](https://tex.z-dn.net/?f=F%28x%29%20%3D%20F%28x%29%20-%20a.%20So%3C%2Fp%3E%3Cp%3E%5Btex%5DF%28x%29%20%3D%202%5E%7Bx%2B2%7D)
Shifting 6 units down
![F(x) = 2^{x+2} - 6](https://tex.z-dn.net/?f=F%28x%29%20%3D%202%5E%7Bx%2B2%7D%20-%206)
Answer/Step-by-step explanation:
÷ 2 ÷ 4
- -4 x -4 x -4 = -64
- -64 ÷ 2 = -32
- -32 ÷ 4 = -8